The Comparative Analysis of Face-To-Face, Distant, and Blended Learning in English Language Teaching - Podoliak, Mykhailo (Register Journal, 2022)
Distant and blended learning are modern educational methodologies, gaining popularity among many teachers and students worldwide. These teaching methods became more popular owing to COVID 19 and quarantine measures in education. In this article, we set the aim to compare three methods of teaching a foreign language in the University: traditional (face-to-face), distant and blended, and determine which method yields the best results. The research lasted for one semester and consisted of the following stages: initial – the preparation for experiment; educational – the usage of the selected teaching method; final – collecting results and their analysis. The research results have demonstrated that the blended approach of language teaching proved to be more effective in both the results of the tests. Therefore, blended learning proved to be an effective way of teaching a foreign language in the University.Keywords: traditional learning, distant learning, blended learning, English language teaching.